2007
DOI: 10.1111/j.1365-2486.2007.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent decline in precipitation and tree growth in the eastern Mediterranean

Abstract: We present evidence of a recent drying in the eastern Mediterranean, based on weather and tree-ring data for Samos, an island of the eastern Aegean Sea. Rainfall declined rapidly after the late 1970s following trends for the entire Mediterranean and was associated with reduced tree-ring width in Pinus brutia. The most recent decline led to the lowest annual radial stem increment after the last 100 years (as far as records reach). As moisture availability decreased best correlations of tree growth with rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
196
1
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(230 citation statements)
references
References 29 publications
(42 reference statements)
19
196
1
14
Order By: Relevance
“…A reduced growth rate in response to declining water availability is a universally observed plant response (Kelliher et al, 1980;Osmond et al, 1987;Oberhuber et al, 1998;Sarris et al, 2007). In most GDEs rainfall and groundwater provide important supplies of water, and the ratio of rainfallto-groundwater uptake varies spatially and temporally.…”
Section: Effects Of Groundwater On Growth and Dendrochronological Traitsmentioning
confidence: 99%
“…A reduced growth rate in response to declining water availability is a universally observed plant response (Kelliher et al, 1980;Osmond et al, 1987;Oberhuber et al, 1998;Sarris et al, 2007). In most GDEs rainfall and groundwater provide important supplies of water, and the ratio of rainfallto-groundwater uptake varies spatially and temporally.…”
Section: Effects Of Groundwater On Growth and Dendrochronological Traitsmentioning
confidence: 99%
“…Despite these adaptations, MTFs have been plagued by chronic stress during recent periods of protracted drought conditions (Carnicer et al 2011). This has translated to extensive crown dieback (Lloret et al 2004) and declines in both growth (Jump et al 2006;Sarris et al 2007) and tree health (Raftoyannis et al 2008) in the Mediterranean basin. Many dominant tree species within MTFs in the South-West of Western Australia (SWWA) have shown similar symptoms in recent decades (Archibald et al 2005;Auclair 1992;Hooper 2009), corresponding with a long-term decline in rainfall (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, drought effects on growth may be time-dependent. In Pinus 3 halepenis Sarris et al (2007) reported that the growth response to drought was 48 more extended under low soil moisture conditions than under less xeric situations.…”
mentioning
confidence: 99%